2018
DOI: 10.18203/2394-6040.ijcmph20180213
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ perception on factors of early marriage among the Urhobos in Delta State of Nigeria

Abstract: Early marriage forces girls into adulthood before they are emotionally and physically matured, and it has harmful effects on their health, educational, economic and social development. In many countries, 18 years is the legal age of marriage and Nigeria has made a constitutional effort to establish same as a minimum age for marriage. This narrative review examined the causes and consequences of early marriage with a view to establish framework to assess the perception on factors among Urhobos in Nigeria. Unpub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In the narrative review preceding this report, the potential causes and consequences of early child marriage have been highlighted. [2][3][4][5][6][7][8] The responses affirm that there is significant disagreement on causes of early marriage that boils down to perceptions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the narrative review preceding this report, the potential causes and consequences of early child marriage have been highlighted. [2][3][4][5][6][7][8] The responses affirm that there is significant disagreement on causes of early marriage that boils down to perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of data on perception of parents suggests that educational intervention needs to start with community needs assessment". 2 The objective of this study is to investigate the perceptions of parents on concepts as well as causes and consequences of early marriage as a public health problem. It is hoped that this may provide data that could help to change parents" attitude towards practices, customs and traditions against early marriage.…”
Section: Introductionmentioning
confidence: 99%
“…Undoubtedly, large investments are needed to overcome people's perceptions to enrich the culture of gender roles and women's dependence on men. Early marriage that occurs in Nigeria is caused by gender discrimination, pregnancy before marriage, low socioeconomic status and parental perceptions [23]. The factors that cause early marriage need to be further identified for each community so that it can appropriately cope with the impacts.…”
Section: Relationship Between Environment and Attitudes With Adolesce...mentioning
confidence: 99%
“…This statement is supported by Nour ( 2010), who reported that marriage before 18 years has many effects on girls' health, such as the increased risk for sexually transmitted diseases, death during childbirth, obstetric fistulas. Other studies reveal that getting married at a young age leads to psychological problems and suffering because a little girl or boy cannot make rational decisions regarding critical issues, including conflicts (Abdul et al, 2018).…”
Section: Awareness Of Early Marriage and Its Impact On Girlsmentioning
confidence: 99%